2010
DOI: 10.1590/s1519-566x2010000600017
|View full text |Cite
|
Sign up to set email alerts
|

Aging and food source effects on mandibular stylets teeth wear of phytophagous stink bug (Heteroptera: Pentatomidae)

Abstract: -Studies were conducted to test the effect of age and food sources on wear of the mandibular teeth of the phytophagous pentatomid, Euschistus heros (F.). The total length (μm) of the area bearing the mandibular teeth, the length of the 1st tooth, and the height of the 2nd tooth for teneral (< 1 day-old) adults were signifi cantly greater than that of adults fed on natural [green bean, Phaseolus vulgaris pods, raw shelled peanuts, Arachis hypogaea, and mature soybean, Glycine max seeds] for 30 or 60 days. Adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
3
16
0
Order By: Relevance
“…To our knowledge, this is the first time that the detailed mouthpart morphology and feeding performance in a member of Pentatomidae have been reported together. The modified mouthparts of E. fullo have a number of morphological similarities to those heteropteran species described previously [17,19,22,37,44,[48][49][50][51][52][53][54][55], but our study revealed some new and interesting features that differ from those of other true bugs, and provide a better understanding of the feeding strategies and the sensory systems of E. fullo.…”
Section: Discussionsupporting
confidence: 60%
“…To our knowledge, this is the first time that the detailed mouthpart morphology and feeding performance in a member of Pentatomidae have been reported together. The modified mouthparts of E. fullo have a number of morphological similarities to those heteropteran species described previously [17,19,22,37,44,[48][49][50][51][52][53][54][55], but our study revealed some new and interesting features that differ from those of other true bugs, and provide a better understanding of the feeding strategies and the sensory systems of E. fullo.…”
Section: Discussionsupporting
confidence: 60%
“…nigricornis Stål, the teeth in P . sibiricus are relatively prominent and stout, but they differ from those of other heteropteran in number and pattern [15,29,32,33,38,39]. The sharp ends of the mandibular stylet are specialized to pierce plant tissues while probing.…”
Section: Discussionmentioning
confidence: 99%
“…Mandible wear may not be a problem for S. endius because an individual only chews out of a host once, at emergence, and S. endius are not known to feed on solids as adults. Many previously documented cases of mouthpart wear are in insects that repeatedly consume a food source with high intractability, e.g., mandibles of a coleopteran feeding on willow leaves (Raupp 1985), stylets of a hemipteran feeding on leaves, stems and insect prey (Roitberg et al 2005), mandibles of a caterpillar feeding on grasses containing silica (Massey and Hartley 2009), and stylets of a hemipteran feeding on legume pods and seeds (Depieri et al 2010). Among parasitoid wasps, those that egress from a "hard host substrate, typically in wood," frequently show wear of their mandibles (Quicke et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of relative intractability of the external surface as a method of resistance has been especially well-documented in plants, where a hard exterior can successfully deter herbivory, but the concept also applies to host-parasite and prey-predator interactions. Toughness may decrease the chance that a consumer can reach the nutritious parts, decrease digestibility (Massey and Hartley 2009), increase the time required to consume and digest (Clissold et al 2009, Schofield et al 2011, and result in more wear on mouth parts, both mandibles and stylets (Raupp 1985, Roitberg et al 2005, Depieri et al 2010. In apparent coevolution to such wear, some insect consumers have metal ions, such as zinc or manganese, incorporated into their outer cuticle (Schofield et al 2002, Quicke et al 1998; however, wear is still often evident in older insects (Schofield et al 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation